The Application of Foliar Fertilizer For Tea Crops As Alternative Fertilization Method During Dry Period Condition In Pagilaran Tea Estate - Prapto Yudono; Djoko Muljanto (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2000)
-